PERKEMBANGAN MORFOLOGI DAN SIFAT FISIK BUAH PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Mulyadi Mulyadi; Aslim Rasyad; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the change pattern of  morphological and  physical traits of palm oil fruitsduring the fruit development until the time to harvest. This researchhas been conducted at PT. Panca Surya Garden’s Research Farm located in Kubang Raya, Kampar and Plant Physiology Laboratory, Faculty of Agriculture, University of Riau Pekanbaru from February to August 2016.Sixty fruit bunchs which antheses at the same day were selected at random from 7 years old oil palm trees. The fruit bunches were hand pollinated at 18 March 2016 and each was covered by pollination bag. Beginningat 30 to 120 days after pollination (DAP), 3 fruits bunches were harvested at 15 day interval. Then from 125 DAP to 185 DAP the fruit bunch were harvested every 5 days interval. The change of morphological and physical traits were observed such as fresh bunch weight, fresh fruit weight per bunch, mesocarp thickness, fruit diameter, fruit volume andfruit moisture content, and fruit color. Showed that the increase of bunch weight, fresh fruit weight per bunch, fresh fruit weight occurred at the same pattern. Fruit fresh weight and dry weight increase steadily from 30 DAP  and reached the maximum values at about 170 DAP, then decreased slightly until 185 DAP. The fruit water content increased slowly from 30 to 45 DAP, then decreased progressively untul 150 DAP and finally decreased very rapidly  from 150 to 180 DAP. Fruit color changed from dark purple to red purple and finally at harvest the color change to yellow red. Keywords : palm oil, bunch weight, fresh fruit weight, fruit dry weight